2015
DOI: 10.1149/2.0051506jes
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Improvement in Cyclic Voltammetry Stripping Analysis of Thiourea Concentration in Copper Plating Baths

Abstract: Cyclic voltammetry stripping (CVS) has been regarded as a powerful tool for monitoring the concentrations of organic additives in plating baths. In this study, the dilution titration (DT) method of CVS was modified to improve the measurement accuracy of thiourea (TU) concentrations in Cu plating baths. The conventional DT-CVS method cannot guarantee high accuracy because the electrochemical behavior of TU is concentration and potential dependent, which can cause disturbances in the response signals. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…However, S. Choe pointed out that the enhancement of the electrochemical signal by SPS is interfered with the signal of MPS, the amount of SPS interfered with MPS may affect the behavior of electrodeposition solution. 21 Unfortunately, ECI did not show any void free evidences in their publications. On the other hand, S. Choe et al developed a two-step CVS analysis in which the total concentration and conversion ratio of SPS and MPS were separately determined.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…However, S. Choe pointed out that the enhancement of the electrochemical signal by SPS is interfered with the signal of MPS, the amount of SPS interfered with MPS may affect the behavior of electrodeposition solution. 21 Unfortunately, ECI did not show any void free evidences in their publications. On the other hand, S. Choe et al developed a two-step CVS analysis in which the total concentration and conversion ratio of SPS and MPS were separately determined.…”
mentioning
confidence: 98%
“…The concentration of the accelerators, especially SPS is typically determined by CVS method [16][17][18][19][20][21][22] in combination with linear approximation technique (LAT) or modified linear approximation technique (MLAT). 20,22 G. Chalyt et al of ECI Technology published the method for determining the concentration of three organic additives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in order to monitor the concentration change, various methods for analyzing the concentration of decomposed organic additives were suggested. [32][33][34][35][36] As a result of SPS decomposition via chemical and electrochemical pathways, it has been suggested that PDS are produced as final breakdown products, whereas MPS, sulfopropanol, sulfoxide, SPS(O), and SPS(O 2 ) are formed as intermediates. 24 Once MPS is produced, the cathodes becomes depolarized, because MPS has a greater acceleration effect than does SPS.…”
mentioning
confidence: 99%
“…35,36 Accurate monitoring of these species followed by precise feedback ensures the solution reliability during the long-term plating operation. [37][38][39][40][41][42] We proposed novel electrochemical methods that enable the in-situ and real-time monitoring of the concentration of SPS/MPS couple, 39 PEG molecular weight, 42 and the thiourea concentration 37 in a real-scale Cu plating bath by using cyclic voltammetry stripping (CVS). Determination of I − has been widely researched in many fields.…”
mentioning
confidence: 99%